Erythrocyte Fraction in Thrombi Is Increased with Serum Iron by Influencing Fibrin Networks via Oxidative Stress. (24th December 2021) - Liu, Mingli; Chen, Minghui; Hao, Zhongfei; Li, Qingbin; Feng, Yan; Li, Yongli; Li, Ruiyan
Abstract : Objective. This study investigated whether the erythrocyte fraction in thrombi would be increased with serum iron via oxidative stress. Methods. This study retrospectively enrolled patients with acute ischemic stroke treated using endovascular treatment in a single stroke center from October to December 2019. We examined the relationship between serum iron and erythrocyte-rich thrombi and the correlation of serum iron and the erythrocyte fraction in thrombi using clinical samples. Experiments in vivo and in vitro were performed to investigate the influence of oxidative stress on the correlation between serum iron concentration and erythrocyte fraction in thrombi. Results . We found from the clinical samples that serum iron concentration was related to erythrocyte-rich thrombi and positively associated with the erythrocyte fraction in thrombi in vivo . Further, the tightness of the fibrin networks regulating the erythrocyte fraction in thrombi was increased with serum iron concentration in vivo . Additionally, the oxidative stress level was increased with serum iron concentration in vivo . Moreover, we found that the tightness of the fibrin networks increased with higher oxidative stress levels in vitro . Lastly, experiments in vivo with inhibiting oxidative stress showed that the erythrocyte fraction in thrombi and the tightness of fibrin networks significantly increased in the iron group than those in the iron with oxidative stress inhibitor group and control group. Conclusions. Oxidative stress played a role in the process that the erythrocyte fraction in thrombi was increased with serum iron by influencing fibrin networks.